Covid-19 pandemic and unemployment in Malaysia: A case study from Sabah - Nga Lay Hui @ Janice Nga; Wijaya Kamal Ramlan; Shafinaz Naim (UTS ePress, 2021)
Covid-19 not only exposed the vulnerability of most industries especially industries that relies on air travel and tourism but resulted in the exponential increase of unemployment in Malaysia. At the same time, online business or trade and ‘GIG’ economy increased exponentially. The sudden and unexpected loss of jobs had dire consequences for many people. This paper examines how policies enacted during the Covid-19 pandemic affected unemployment in Malaysia by focussing on the situation in Sabah, one of the three remaining partners in the formation of Malaysia. It draws on data from the Family, Women and Youth Survey conducted online towards the end of 2020, as well as secondary data. The study shows that hardship has been faced by many people, especially those previously in professional roles, and those who are younger. The widespread damage to the economy, and to social cohesion, will require significant collaboration between business and industry, the government and the people.